Dynamic simulation of wind turbine planetary gear systems with gearbox body flexibility - Xu, Xiangyang (Strojniški vestnik, 2016)
Gearbox body flexibility has a great influence on the dynamic response and load sharing among the planetary gears. In this paper, through investigating the coupling boundary conditions between planetary gears transmission subsystem and the gearbox body subsystem, a new dynamic model that integrates gearbox body flexible supporting stiffness is developed to simulate the effects of gearbox body flexibility on the dynamic response and the dynamic load sharing. The numerical results demonstrate that the dynamic transmission error and the dynamic mesh force are obviously lower in the system with the gearbox body flexibility than without it. Furthermore, peak position also gradually moves towards to the lower frequency when gearbox body flexibility is included. In addition, the dynamic loading factor tends to be decreased when gearbox body flexibility is taken into account, which is also verified by experiments conducted on a planetary gear test rig.
Keywords: dinamične lastnosti; gonila vetrne turbine; planetna gonila; porazdelitev obremenitev; sklopljen dinamični model; upogljivost ohišja gonil